(untitled) (SCIÉNDO INGENIUM, 2026)
The purpose of this analysis was to examine occupational risk management at Frigotech del Perú S.A.C., in order to identify the most vulnerable areas, assess risk exposure, and establish control methodologies that contribute to reducing accidents. The study was framed within a descriptive approach, with a longitudinal, non-experimental design. Tools such as the initial diagnosis, the IPERC matrix, the annual OSH plan, and OSH-related statistics were used. The results showed that the highest level of risk was concentrated in the Operations area. Based on this diagnosis, a SGSST plan was implemented, in accordance with Law No. 29783. As a result, between September 2024 and February 2025, the Accident Rate was reduced from 61% to 28%, the Frequency Rate fell from 61% to 28%, and the Severity Rate fell from 25% to 6%. These results show that effective risk management allows for hazard identification, risk assessment, and the application of appropriate corrective measures, thus contributing to a safe and healthy work environment.